Estimation of NLR in COVID-19 Patients in a Tertiary Care Center& determining its significance as a prognostic marker - Preeti Bajaj; Devangana Rajyaguru; Aakash Gupta; Gayatri Soneta (Tropical Journal of Pathology and Microbiology, 2022)
Introduction: The rapid spread and serious harm of COVID-19 makes it urgent to continuouslyimprove and enrich its clinical diagnosis and treatment research. Using a simple test like NLR forassessing the risk of mortality and early identification of severe cases will help in preventing life-threatening complications in COVID-19 patients. Objectives: To study trends of NLR counts inCOVID 19 patients and the correlation between NLR and COVID-19 severity. Methods: A total of137 random subjects whose blood samples were collected on the day of admission, on the 3rd dayand on the 6th day of admission were included in the study. NLR was calculated as simplyneutrophils /lymphocytes and trends were studied. Results: An average of all three NLR counts forthe patients revealed an overall decreasing trend in cases of survivors, whereas an overall upwardtrend was noted in the non-survivors. All of the patients admitted to the COVID ICU, that is thosewho had severe disease, showed a high NLR value of >3, in at least one of the three tests. Conclusion: The NLR was the most promising predictive factor for critical illness incidence ofCOVID-19 pneumonia. Early application of NLR will be beneficial for patient management and reliefof medical resource shortage.